The predictors of the intention to receive Covid-19 vaccine using the health belief model and theory of planned behavior in South Khorasan province - Zahra Khazir; Hamideh Kouhpeikar; Zohreh Rahaei; Moradali Zareipour; Saeid Dashti; Monireh Gholamian (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Widespread vaccination coverage in the shortest time is one of the most effective ways for controlling the COVID-19 pandemic. Factors affecting people's intention to get the COVID-19 vaccine are of great importance. The present study aimed to investigate the predictors of the intention to receive the Covid-19 vaccine based on the constructs of the health belief model (HBM) and theory of planned behavior (TPB) in South Khorasan Province. MATERIALS AND METHODS: In this cross-sectional-analytical study, 320 people over 18 years in South Khorasan province were randomly selected by cluster sampling method in 2021. The data was collected by a researcher-made questionnaire, including demographic information (9 questions), and the constructs of the health belief model (19 questions), and the theory of planned behavior (13 questions), using the self-report method. Finally, data were analyzed using t-test, ANOVA, linear regression, and Pearson correlation tests. RESULTS: The mean age of the study participants was 36.57 ± 11.56 with a range of 18-66 years. In the regression model, perceived susceptibility (β = 0.247, P = 0.003), perceived severity (β = 0.247, P = 0.003) from HBM, attitude (β = 0.247, P = 0.003), and perceived behavioral control (β = 0.247, P = 0.003) from TPB were significant predictors of the intention to get the Covid-19 vaccine. The constructs of the two models were able to explain 33% of the variance of the intention to receive the Covid-19 vaccine. CONCLUSIONS: The study findings reveal that HBM and TPB can predict factors affecting an individual's intention to receive the vaccine. The results can be utilized to design interventions with the aim of increasing vaccine uptake.